Presensi Online Menggunakan Global Positioning System untuk Penilaian Kinerja Pegawai Berdasarkan Metode Simple Additive Weighting - Syaiful Khoir; Anton Yudhana; Sunardi Sunardi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Cooperative for Savings and Loans and Sharia Financing BMT Insan Mandiri is a sharia financial institution that is a cooperative in Central Java Province. Insan Mandiri has several branches in Central Java with more than 50 employee. Insan Mandiri uses manual attendance to record attendance and return of employees. The use of manual attendance currently being implemented feels ineffective because it is easy to fake and makes it difficult to calculate attendance and prepare attendance reports.This research aim to designing and creating an Android-based presence application to simplify the attendance process and making attendance reports through the website application. The attendance application is made with two applications. The first application is made with a website with the PHP programming language which are used to input employee data, applicable working hours, and create attendance reports along with the results of the analysis of employee performance levels. The second application is an Android-based built using the Java programming language with the functions as a tool for presence. This application will send attendance data to the server in the form of attendance hours or returns and the location of the employee makes a presence in the form of location coordinate data taken from the smartphone Global Positioning System (GPS) used by employees. This research was conducted by applying the Simple Additive Weighting algorithm which is run on a website application. This algorithm will calculate the sum with the weighted addition method by normalizing the matrix of all alternative ratings sent by the Android application. From the research conducted, it can assist the company in determining the level of employee performance. Furthermore, the system developed is called the presence and performance appraisal system. Testing the attendance application and performance assessment using the SAW method which was completed, obtained accuracy of 60.1% valid data and 39.9% non valid. The accuracy value obtained is low because there are several alternatives that have the same value, causing the alternative order to be different. The system application can run online, Android mobile and the website can be integrated to evaluate employee performance, and can simplify the process of recording employee attendance and return. Based on the black box test, the website and Android applications were 100% running as expected and no errors were found in the software development process. Based on the results of the beta test, 80.3% of respondents agree with the functionality of the application system and the rest are still unsure.